2016
DOI: 10.1007/s40261-015-0370-y
|View full text |Cite|
|
Sign up to set email alerts
|

The Efficacy of Perindopril/Amlodipine in Reaching Blood Pressure Targets: Results of the CONTROL Study

Abstract: We found that a fixed combination of perindopril/amlodipine is effective in controlling BP in patients with essential hypertension, with older age, male gender, and diabetes mellitus being independent risk factors for less BP control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…The rate of cough leading to discontinuation of treatment was 1/10 (0.1%). In other studies, the incidence of patients experiencing dry cough while using perindopril/amlodipine FDC was reported as 1/ 13 in the study by Liakos et al (2017), 4/25 in Vlachopoulos et al (2016, 1/7 in Nagy (2013), 5% in Abdelhady et al (2016), and 0.2% in Forster and Dézsi (2016).…”
Section: Safetymentioning
confidence: 79%
See 3 more Smart Citations
“…The rate of cough leading to discontinuation of treatment was 1/10 (0.1%). In other studies, the incidence of patients experiencing dry cough while using perindopril/amlodipine FDC was reported as 1/ 13 in the study by Liakos et al (2017), 4/25 in Vlachopoulos et al (2016, 1/7 in Nagy (2013), 5% in Abdelhady et al (2016), and 0.2% in Forster and Dézsi (2016).…”
Section: Safetymentioning
confidence: 79%
“…Most studies examined the therapeutic efficacy of perindopril/amlodipine FDC at doses of 5/5, 5/10, 10/5, and 10/10 mg in untreated or uncontrolled hypertensive patients with previous treatment. Table 1 shows the effectiveness in reducing BP and increasing the BP control rates in the total hypertensive population of the studies ( Nagy, 2013 ; Manolis et al, 2015 ; Abdelhady et al, 2016 ; Forster and Dézsi, 2016 ; Vlachopoulos et al, 2016 ; Liakos et al, 2017 ; Fleig et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There are new laboratory data on the effects of telmisartan on oxidative stress, myocardial ischemia, and immune response. Authors have observed an increase in catalase and superoxide dismutase expression levels under telmisartan treatment, with a decrease in injury and oxidative biomarker levels, and have concluded that telmisartan reduced 18 .…”
Section: Discussionmentioning
confidence: 99%